The influence of high‐resolution wind stress field on the power input to near‐inertial motions in the ocean. Issue 18 (23rd September 2013) - Rimac, Antonija; von Storch, Jin‐Song; Eden, Carsten; Haak, Helmuth
Abstract : [1] The wind power input to near‐inertial (NI) motions is studied using a global eddy‐permitting ocean general circulation model. The model is forced by high‐ (1‐hourly, at 0.35° resolution) and low‐resolution (6‐hourly, at 1.875° resolution) wind data. A change from low‐ to high‐resolution forcing results in an increase in NI kinetic energy by a factor three and raises the wind‐generated power input to NI motions from 0.3 TW to 1.1 TW. Time and space filtering of the wind fields yield less kinetic energy, with a larger drop from time filtering. This strong sensitivity to wind forcing points to a possible underestimation of the wind‐generated energy available for deep ocean mixing in previous studies based on low‐resolution winds. Key Points: Near‐inertial motions in the ocean are generated by hourly wind forcing Temporal resolution of the winds has a stronger effect than spatial resolution The total wind‐induced power input to near‐inertial motions is 1.1 TW